Exterior Tensor Product of Perverse Sheaves - Lyubashenko, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
Under certain assumptions, we prove that the Deligne tensor product of the categories of constructible perverse sheaves on pseudomanifolds X and Y is the category of constructible perverse sheaves on X×Y. The functor of the exterior Deligne tensor product is identified with the exterior geometric tensor product.